Literacy: A Challenge in the Training of Teachers in Basic Education: - Mejía Reyes, Brenda; García Zárate, María de Lourdes (Emerging Trends in Education, 2021)
Literacy is the most recent concept applied to reading and writing from educational research, which understands it from its linguistic and psycholinguistic perspective, and adds the functional aspect with a sociocultural approach. In Mexico, this process has been called “alfabetización”, and as such, it is included in basic education study programs; thus, determining the perspective from which interventions will be developed for its teaching. In view of this, the interest arises to identify what do educators in training know about literacy. For this, a questionnaire with ten multiple-choice items was designed based on the perspective of Ferreiro (1998) and Cassany (2009). It was applied in the form of an online survey to 51 students of the degree in preschool education from two Normal schools in San Luis Potosí, in the first one for the pilot test and in the second one for the application of the survey once the instrument was approved. The results show that the educators in training make use of various written materials for the development of literacy. However, they have little conceptual clarity about the term literacy itself.